2019
DOI: 10.1681/asn.2018080853
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Inhibition of VEGF Signaling and Associated Nephrotoxicities

Abstract: Inhibition of vascular endothelial growth factor A (VEGFA)/vascular endothelial growth factor receptor 2 (VEGFR2) signaling is a common therapeutic strategy in oncology, with new drugs continuously in development. In this review, we consider the experimental and clinical evidence behind the diverse nephrotoxicities associated with the inhibition of this pathway. We also review the renal effects of VEGF inhibition's mediation of key downstream signaling pathways, specifically MAPK/ ERK1/2, endothelial nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
153
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(171 citation statements)
references
References 108 publications
1
153
0
2
Order By: Relevance
“…Podocyte-specific VEGF164 overexpression in adult mice demonstrated that VEGF-A, activating VEGFR2 in podocytes, can induce reversible changes on the slit diaphragm proteins contributing to the abnormalities in the glomerular filtration barrier, as noted in the diabetic kidney [39]. To contrast, VEGF-A also has shown protective effects in acute models of renal injury, although the mechanisms involved have not been completely elucidated yet [6]. Concerning the BTBR ob/ob model, renal vegf-a gene expression was significantly increased at 8 weeks, coincidentally with the onset of the diabetes, but its gene expression was downregulated thereafter, showing no differences to non-diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Podocyte-specific VEGF164 overexpression in adult mice demonstrated that VEGF-A, activating VEGFR2 in podocytes, can induce reversible changes on the slit diaphragm proteins contributing to the abnormalities in the glomerular filtration barrier, as noted in the diabetic kidney [39]. To contrast, VEGF-A also has shown protective effects in acute models of renal injury, although the mechanisms involved have not been completely elucidated yet [6]. Concerning the BTBR ob/ob model, renal vegf-a gene expression was significantly increased at 8 weeks, coincidentally with the onset of the diabetes, but its gene expression was downregulated thereafter, showing no differences to non-diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular endothelial growth factor receptor 2 (VEGFR2) is expressed in several renal cells, including podocytes and tubular epithelial cells [4,5]. This receptor is activated in experimental and human renal diseases [6], including DN [7]. Most of the studies about VEGFR2 signaling have been done in cell carcinomas [8].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with an anti-VEGF 165 antibody results in a significant attenuation of albuminuria in diabetic mice and rats [1,14,18]. However, anti-VEGF treatment in the prevention of microvascular disease is associated with serious obstacles, since, for example, VEGF 165 antibodies cause renal damage and hypertension in lung cancer patients, and nephrotoxicity commonly occurs after anti-VEGF therapy as previously reviewed [19,20]. VEGF has been observed to have an important role in maintaining the endothelial integrity because, anti-VEGF therapy in patients with solid tumours as well as conditional ablation of VEGF in adult mice led to microangiopathy [21,22].…”
mentioning
confidence: 98%
“…In recent years, with the use of vascular endothelial growth factor A (VEGFA) inhibitor in oncology, the number of patients with kidney disease is increasing, mainly manifested as thrombotic microangiopathy, minimal change nephropathy, and collapsing focal segmental glomerulosclerosis [8,15,16], however, there is no membrane nephropathy reported. Additionally, rituximab, a B cell-target monoclonal antibody, which has become the rst line therapy in IMN according to KDIGO CLINICAL PRACTICE GUIDELINE ON GLOMERULAR DISEASES 2020, showed its ability to decrease the VEGFA level in plasma in patients with recurrent mantle cell lymphoma [17].…”
Section: Discussionmentioning
confidence: 99%